Pemanfaatan Media Pembelajaran di Kelas V Sekolah Dasar Negeri 1 Sumbang - Utami, Nadiya Rakhma; Bintaro, Tri Yuliansyah (ISLAMIKA, 2024)
The use of media in teaching and learning activities is intended as a complement and supporting facility for teachers in conveying education and information, not to replace the role of the teacher or the teacher’s way of teaching. Generally, learning media is used for the purpose of facilitating the delivery of information and education from teachers to students, so that this material is easier to understand and attracts students’ attention and is more enjoyable. The purpose of this research is to find out the utilization of learning media in class V of State Elementary School 1 Sumbang, find out the obstacles to the utilization of learning media, and find out the solutions provided from the school both from the principal and class V teachers so that learning media can be utilized more optimally. The method used in this research is qualitative with data collection techniques through observation, interviews, and documentation. The informants in this study were the principal, grade V teacher, and grade V students. The results of this study indicate that learning media in class V of State Elementary School 1 Sumbang has been utilized during learning, but its utilization is still not optimal. Optimal utilization of learning media can facilitate teachers in teaching and students can also more easily understand learning.